The basics of speech : learning to be a competent communicator - Galvin, Kathleen M. (National Textbook Co., 1999)
Introduces interpersonal and group communication, public speaking, debate, parliamentary procedure, and oral interpretation. Includes activities, checklists, evaluation forms, suggested speech topics, and literature for oral interpretation.